The Effect of Giving Mung Bean Juice to Increasing Hemoglobin Levels in Pregnant Women at the Sungai Kapih Health Center in Samarinda - Andi Siti Ridha Wahyuni; Umi Kalsum; Nursyahid Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nutritional anemia is a health problem that contributes to the high maternal mortality rate. How to treat anemia with Fe tablets and increase intake of food sources of Fe. The purpose of this study was to determine the effect of green bean juice on increasing hemoglobin levels in pregnant women. The research method uses a quasi experiment with a two group pretest - posttest design. The total sample is 24 respondents. The sampling technique uses accidental sampling. Independent sample t-test results (pvalue = 0.002). There is a difference in the increase in hemoglobin levels before and after the intervention. Discussion: Green beans have an iron content of 6.74 mg per 100 g of green beans which are useful in the formation of red blood cells. Giving green bean juice is more effective for increasing hemoglobin levels of pregnant women.